2019
DOI: 10.1016/j.physb.2019.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of size, temperature and strain rate on dislocation density and deformation mechanisms in Cu nanowires

Abstract: In the present study, molecular dynamics (MD) simulations have been performed to understand the effect of nanowire size, temperature and strain rate on the variations in dislocation density and deformation mechanisms in <100> Cu nanowires. The nanowire size has been varied in the range 1.446-43.38 nm with a constant length of 21.69 nm. Different temperatures varying from 10 K to 700 K and strain rates in the range of 5 × 10 7 -1 × 10 9 s −1 have been considered. For all the conditions, the variations in disloc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Yaghoobi and Voyiadjis [64] MD simulations on the Ni nanopillars showed that the deformation dominant mechanism is independent of the strain value and is affected only by the pillar size. Rohith et al's [68] MD simulation on the tensile behaviour of Cu nanowires showed two stages irrespective of deformation temperature and strain rates; dislocation exhaustion at early stages of deformation followed by dislocation starvation at high strains. Korchuganov et al [69] proposed an atomic model for the nucleation of dislocation and twins based on the local reversible fcc → bcc → fcc transformation.…”
Section: Introductionmentioning
confidence: 99%
“…Yaghoobi and Voyiadjis [64] MD simulations on the Ni nanopillars showed that the deformation dominant mechanism is independent of the strain value and is affected only by the pillar size. Rohith et al's [68] MD simulation on the tensile behaviour of Cu nanowires showed two stages irrespective of deformation temperature and strain rates; dislocation exhaustion at early stages of deformation followed by dislocation starvation at high strains. Korchuganov et al [69] proposed an atomic model for the nucleation of dislocation and twins based on the local reversible fcc → bcc → fcc transformation.…”
Section: Introductionmentioning
confidence: 99%
“…New grains readily formed from the subgrains of the dislocation networks at their expense. [35,36] The reduction in the whisker diameter and obstruction of nucleated dislocations from escaping to the surface by the newly formed grains are considered to both maintain the recrystallization process and increase the tensile strength of the tested whisker. If the required stress concentration is not maintained (e.g., by decreasing the strain rate), the strengthening cycle is terminated.…”
Section: Observed Modes Of Deformation In the Current Study And Propo...mentioning
confidence: 99%
“…In recent years, [001]-oriented Cu NWs have garnered attention for their unique mechanical, electrical, optical, catalytic, and thermal properties. [1][2][3][4][5][6][7][8]11,39,43 However, their performance depends on the pre-existing native oxide shell layer on their free surfaces. Therefore, our research focuses solely on [001]-oriented Cu NWs under tensile loading.…”
Section: Simulation Detailsmentioning
confidence: 99%